Anelastic characterization and superconducting properties of RuSr2GdCu2O8+delta - Gimenez, J. M. A. [UNESP]; Grandini, Carlos Roberto [UNESP]; Jurelo, A. R.; Goes, M. S. [UNESP] (Soc Espanola Ceramica Vidrio, 2008)
Since the discovery of the high Tc superconductors, many researches have been carried out on the different properties of these materials, especially oil the transition temperature into the superconducting state. The rutheno-cuprates belong to a new class of composites, which were synthesized for the first time by Bauernfeind in 1995. Bernhard and collaborators tors discovered, in 1999, the coexistence of the ferromagnetism and the superconductivity in this phase, which is known antagonistic phenomenon in the electromagnetism due to spin-charge interactions established in these state. However, the physical nature of the superconducting and magnetic states is still very obscure. The non-stoichiometric (interstitial) oxygen is considered as a possible cause for the non-uniformity of the sample properties. In this paper, results of mechanical spectroscopy in Ru-1212 samples are presented showing complex anelastic spectra, which were attributed to the mobility of the interstitial oxygen atoms in the Ru-1212 lattice.
Keywords: Mechanical Spectroscopy; Ru-1212; Oxygen Mobility